Rancang Bangun Sistem Informasi Pengelolaan Aktiva Tetap berbasi website di PT Ma’soem Cikalang - Aa Rizkon; Dwi Atmoko (Ma'soem University, 2022)
PT. Ma'soem Cikalang Group is a business institution engaged in oil, gas, mineral oil, mineral water and an educational foundation in equipment ownership assets. PT Ma'soem has more than 1000 equipment used to support its operational activities. But in managing the inventory of equipment is still done semi-computerized using Microsoft Excel. Causing problems such as difficulty in performing physical check of equipment with existing data, difficulties in finding information on equipment in the branch office, limited working hours to access equipment information and allowing data loss and data duplication. The analysis conducted in this study includes an analysis of the current system and an analysis of the proposed system. The system design used is the OOAD (Object Oriented Analysis and Design) method approach with the UML (Unified Modeling Language) modeling language. The design of this information system is expected to make it easier for officers to carry out an inventory of equipment, present information on needed equipment wherever and whenever, and minimize data loss and data duplication.